Printed dipole antenna and its arrays for wireless applications - Teju, V; V. P. S Nikhil, P; Pranusha, A; Divya, Ch; Bhanuprakash, G (International Journal of Engineering and Technology, 2018)
This paper proposes single element of micro-stripe antenna having wider bandwidth and also its arrays which are implemented for wire-less applications. In contemplation of wide frequency range of operation, antenna is fed with integrated balun. The single element antenna works under frequency range of 34GHz to 46GHz where reflection loss is less than -10dB and the obtained gain is 2.1 dBi. The linear 8-element array of antenna has been implemented and to obtain low mutual coupling between the elements of antenna a rectangular stub has been implemented. By enforcing the array methodology the not only the overall gain of the antenna has increased but also results in wider scanning angle.Â Â